Designing of Web-based E-Commerce Platform at Jaya Studio - Radityana, I Nengah; Githa, Dwi Putra; Perdana Putra, Yohanes (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 13 No 1 (2025): Vol. 13, No. 1, April 2025DO - 10.24843/JIM.2025.v13.i01.p04, 2025)
Jaya Studio is a music equipment store that still operates using a conventional sales system, requiring customers to visit the location directly for transactions. Designing and building a website-based e-commerce platform integrated with payment gateway services and RajaOngkir helps Jaya Studio provide optimal shopping experiences for customers and reach a wider market. System development using the Agile method makes the work systematic and gradual, meeting both customer and store needs. Customers can view product details including YouTube music equipment demonstration videos without duration limits like on Shopee or Tokopedia e-commerce platforms, providing not just shopping experiences but knowledge about the musical instruments. Testing was conducted using black box and stress test methods. With 100 continuous VUs in the stress test, website performance maintained normal operations with an average of 982 milliseconds over 52 minutes and 30 seconds, with only 5% of response times exceeding 1,663 seconds.